The Technical Efficiency of Engineering Industry Cluster at Hosur. Issue 2 (June 2019) - Bhaskaran, Ethirajan
For inclusive growth and sustainable development Engineering Industries (EIs) in Hosur have adopted the Cluster Development Approach (CDA). The objective is to study the value chain analysis, correlation analysis and data envelopment analysis by finding Technical Efficiency (Ø), Peer Weights (li), Input Slacks (S - ) and Output Slacks (S + ) of 50 EIs. The methodology adopted is data envelopment analysis of output-oriented Banker–Charnes–Cooper Model by taking the number of employment, plant and machinery as input and Gross Value Added (GVA) as output. The non-zero li's represents the weights for efficient clusters. The S > 0 obtained reveals the excess machinery or number of employment (S - ) and shortage in GVA (S + ). To conclude, the variables are highly correlated, and for inclusive growth and sustainable development, the inefficient EI should increase their GVA or decrease the employment or machinery. Moreover, for sustainable development, the EI should strengthen infrastructure interrelationships, technology interrelationships, procurement interrelationships, production interrelationships and marketing interrelationships to decrease costs and to increase productivity and efficiency to compete in the indigenous and export market.